La arquitectura religiosa de Glauco Gresleri: a propósito de su relación con la revista ARA = Glauco Gresleri’s religious architecture: On his relationship with ARA magazine - Fernández Cobián, Esteban (Cuaderno de Notas, 2023)
AbstractDuring his years at the helm of the magazine Chiesa e Quartiere (CH.+Q.), the Italian architect Glauco Gresleri (1930-2016) kept in touch with some Spanish colleagues, although the relationship was never very extensive or intense. After the publication closed in 1968, he began to look for alternative places from which to disseminate his religious production, and he found the perfect place in Spain: the young magazine ARA (Arte Religioso Actual), directed by the Dominican José Manuel de Aguilar. His association with the architect Silvano Varnier dates precisely from that period. Over time, Gresleri and Varnier would become the studio with the greatest presence in ARA during its twenty-seven years of existence. This text offers a critical analysis of the tandem’s religious work, with special emphasis on their international dissemination through their relationship with the Spanish magazine, a little-known aspect of their trajectory.   ResumenDurante sus años al frente de la revista Chiesa e Quartiere (CH.+Q.), el arquitecto italiano Glauco Gresleri (1930-2016) mantuvo contacto con algunos colegas españoles, aunque la relación nunca fue ni muy extensa ni muy intensa. Tras el cierre de la publicación en 1968, comenzó a buscar lugares alternativos desde donde divulgar su producción religiosa, y encontró en España el sitio perfecto: la joven revista ARA (Arte Religioso Actual), dirigida por el dominico José Manuel de Aguilar. Precisamente de esa época data su asociación con el arquitecto Silvano Varnier. Con el tiempo, Gresleri y Varnier se convertirían en el estudio con más presencia en ARA durante sus veintisiete años de vida. Este texto propone un análisis crítico de la obra religiosa del tándem, que incide de modo especial en su difusión internacional a través de la relación con la revista española, un aspecto poco conocido de su trayectoria.